2016
DOI: 10.2147/pgpm.s117014
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic polymorphism as an independent risk factor for frequent hospitalizations in older adults with polypharmacy: a pilot study

Abstract: Pharmacogenetic testing identifies genetic biomarkers that are predictive of individual sensitivity to particular drugs. A significant proportion of medications that are widely prescribed for older adults are metabolized by enzymes that are encoded by highly polymorphic genes. Pharmacogenetic testing is increasingly used to optimize the medication regimen; however, its potential in older adults with polypharmacy has not been systematically explored. Following the initial case–series study, this study hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…The nested case-control study design used in our multivariable analyses is a frequently used approach to address limitations of EHR data. 24,25 Overall, our findings conformed with previous studies that found high potential of EHR in improving quality of dental care delivery 26,27 and outlined existing barriers and pitfalls of secondary analysis of EHR data. [28][29][30] Future work on knowledge extraction from electronic dental records and data science applications incorporating information from large biorepositories will further promote evidencebased dentistry, improve dental education, and facilitate continuous dental care improvement.…”
Section: Discussionsupporting
confidence: 90%
“…The nested case-control study design used in our multivariable analyses is a frequently used approach to address limitations of EHR data. 24,25 Overall, our findings conformed with previous studies that found high potential of EHR in improving quality of dental care delivery 26,27 and outlined existing barriers and pitfalls of secondary analysis of EHR data. [28][29][30] Future work on knowledge extraction from electronic dental records and data science applications incorporating information from large biorepositories will further promote evidencebased dentistry, improve dental education, and facilitate continuous dental care improvement.…”
Section: Discussionsupporting
confidence: 90%
“…Of these the 1,200 Patient Project showed that PGx‐informed prescribing supported by electronic decision support significantly changed prescribing behavior for medications with high pharmacogenomics risk . In addition to these large programs, there are a number of small studies that suggest that a preemptive panel approach leads to a reduction in drug‐related morbidity and costs . The clinical utility of a preemptive PGx panel is investigated using a randomized controlled study design in 8,100 patients recruited from seven EU countries in the PREPARE study coordinated by the U‐PGx consortium…”
Section: Developments Of Pgx Guidelines Within the Next 5 Yearsmentioning
confidence: 99%
“…Results indicate that > 95% of all individuals carry at least one actionable phenotype when tested for a panel of up to 12 genes (including, e.g., CYP2C9 , CYP2C19 , CYP2D6 , SLCO1B1 , and VKORC1 ) [1719]. This panel-based approach has also been favorably evaluated in a number of small pilot studies in a primary care setting [2022].…”
Section: Introductionmentioning
confidence: 99%